Otolith isotopic characterization as a nursery habitat indicator for stone flounder Platichthys bicoloratus. (31st October 2022) - Amano, Yosuke; Otake, Tsuguo; Togashi, Hiroyuki; Wada, Toshihiro; Kasai, Akihide; Kato, Yoshikazu; Yoshimizu, Chikage; Tayasu, Ichiro; Kurita, Yutaka; Shirai, Kotaro
Abstract: Both estuarine and exposed inshore areas along the open coast have been known as important nursery grounds for some flatfish species belonging stone flounder Platichthys bicoloratus. To evaluate the usefulness for distinguishing the nursery habitat types according to different salinity conditions, we examined the otolith stable isotopic ratios ( δ 18 Ootolith and δ 13 Cotolith ) of juvenile stone flounder collected from four habitat types located around Sendai Bay, Miyagi Prefecture, as well as along the coastal areas of neighboring Fukushima Prefecture, northeastern Japan. Muscle tissue stable isotopic ratios ( δ 15 Nmuscle and δ 13 Cmuscle ) of fish used for otolith analyses were also measured for assisting in the interpretation of mechanisms involved in the variations in otolith values. The δ 18 Ootolith values were significantly different among individuals from different types of nursery habitat, likely reflecting salinity of each habitat, namely the value of individuals from the exposed inshore area being the highest, followed in order by those from brackish embayment, lagoon, and river mouth areas. These results suggest that the δ 18 Ootolith precipitated during the juvenile stage can be a reliable proxy to determine the habitat type experienced by each individual on nursery ground after settlement. The δ 13 Cotolith was associated with δ 13 Cmuscle . The δ 13 Cotolith was markedly different between exposed inshore and estuarine habitats, reflecting the difference in major food source organisms between those habitats. Those isotopic characteristics suggest that δ 18 Ootolith and δ 13 Cotolith analysis can provide additional information about nursery habitat type of stone flounder. Highlights: The habitats occupied by juvenile stone flounders were assessed through otolith and muscle isotopic analyses. δ 18 Ootolith reflects salinity of different nursery habitat types. δ 13 Cotolith associated with δ 13 Cmuscle was different among each habitat. Otolith isotopic ratios can be a proxy to determine nursery habitat after settlement.